Equitable food distribution and sustainable development - Dos-Santos, M. J. P. L. (Zero hunger, 2020)
Equitable Food Distribution (EFD) means producing, processing, and distributing food in a timely way to ensure food security for the entire population by the safe and healthy food access to all segments of the population on sustainable conditions from production to the global distribution. This phenomenon could occur in situation of crisis and emergency and also in poor regions with a strong deficit to access to secure and health foods. In both situations contributes to the malnutrition and/or hunger with strong negative impacts in the health of populations where vulnerable people are most affected.